Bound by the clock: The experiences of youth with FASD transitioning to adulthood from child welfare care - Burnside, Linda; Fuchs, Don (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Fetal Alcohol Spectrum Disorder (FASD) is a condition that affects a significant proportion of children and youth in the care of child welfare agencies in Canada. Few studies have heard from the voices of youth with FASD themselves as they are leaving care. This article describes a qualitative study that focuses on the lived experiences of 20 youth with FASD in Manitoba as they were preparing for the transition from child welfare care to adulthood (or had recently emancipated from the system). The experiences and insights of these youth highlight the supports and services required by youth with FASD transitioning out of care, from both the child welfare system and from services for adults with FASD.